dan, terhadap, pada Pengaruh loyalitas merek dan kepercayaan merek terhadap loyalitas pelanggan pada tabungan Gaul iB BPRS Bhakti Sumekar Pusat: Indonesia - Hosna, Fitriyah; Insiyah, Cici' (Jurnal Ekonomika dan Bisnis Islam, 2023)
Brand loyalty is the most important concept in marketing strategy. But to be able to grow brand loyalty must build a brand trust for customers, because brand trust is a determining factor of customer loyalty. This study aims to determine whether there is a partial effect of brand loyalty on customer loyalty, brand trust on customer loyalty, and the simultaneous influence of brand loyalty and brand trust on customer loyalty, and how much influence brand loyalty and brand trust have on customer loyalty in Gaul savings. iB BPRS Bhakti Sumekar Pusat. This research is a quantitative causal comparative study and uses saturated sampling techniques. The data analysis technique used is instrument quality test, classic assumption test, multiple regression test and hypothesis test. The results of this study indicate that there is a partial influence of brand loyalty on customer loyalty. There is no partial effect of Brand Trust on Customer Loyalty. There is a simultaneous effect of Brand Loyalty and Brand Trust on Customer Loyalty. And the magnitude of the influence is equal to 68%.